Prevalence and correlates of exposure to second hand smoke (SHS) among 14 to 15 year old schoolchildren in a medical officer of health area in Sri Lanka - A. M. A. A. P. Alagiyawanna; Esther Queenie Veerasingam; Nick Townsend (BMC, 2018)
Abstract Background Despite reports that Southeast Asia has one of the highest prevalence for childhood exposure to second hand smoke (SHS), there are limited data on SHS exposure among schoolchildren in individual countries in the region, including Sri Lanka. This study aimed to determine the prevalence and correlates of SHS among schoolchildren in a Medical Officer of Health (MOH) region in the country. Methods We conducted a cross-sectional study, sampling from nice schools in one MOH region following a two-stage cluster sample design and probability proportionate to size sampling techniques. Data were obtained through a self-completed anonymous questionnaire on socio-demographic and health behaviour risk factors. We achieved an 89.5% response rate, corresponding to a total of 311 students in the final sample. Results The prevalence of exposure to SHS during the previous week was 17.6% at home and 25.7% in enclosed public places. There were no significant differences in exposure to SHS between sexes. Univariable analysis found that the presence of smokers at home and mother's unemployment status were significantly associated with a higher risk of exposure to SHS at home. These variables remained significant in multivariable analysis. Non-Sinhalese ethnicity and presence of smokers at home were significantly associated with exposure to SHS in public places, in both uni- and multivariable analysis. Unemployment status of mother was also found to be a significant determinant of exposure to SHS in public places in multivariable analysis. Conclusion Despite numerous antismoking activities and strong antismoking legislation, the prevalence of SHS exposure among schoolchildren is higher in enclosed public places than homes. The implementation and enforcement of antismoking legislation is imperative to tackle this and should be supported by the provision of education for schoolchildren and their families on the health risks of SHS. The high-risk groups identified here could be prioritised for preventive programmes.